Electrokinetic ion transport in an asymmetric double-gated nanochannel with a pH-tunable zwitterionic surface. Issue 15 (28th March 2019) - Hsu, Jyh-Ping; Chen, Yu-Min; Lin, Chih-Yuan; Tseng, Shiojenn
Abstract : Bioinspired, artificial functional nanochannels for intelligent molecular and ionic transport control have versatile potential applications in nanofluidics, energy conversion, and controlled drug release. Abstract : Bioinspired, artificial functional nanochannels for intelligent molecular and ionic transport control have versatile potential applications in nanofluidics, energy conversion, and controlled drug release. To simulate the gating and rectification functions of biological ion channels, we model the electrokinetic ion transport phenomenon in an asymmetric double-gated nanochannel having a pH-regulated, zwitterionic surface. Taking account of the effect of electroosmotic flow (EOF), the conductance of the nanochannel and its ion current rectification (ICR) behavior are investigated and the associated mechanisms interpreted. In particular, the influences of the solution pH, the bulk salt concentration, and the base opening radius and the surface curvature of the nanochannel on these behaviors are examined. We show that through adjusting the base opening radius and the surface curvature of a nanochannel, its ICR behavior can be tuned effectively. In addition to proposing underlying mechanisms for the phenomena observed, the results gathered in this study also provide necessary information for designing relevant devices.